2013
DOI: 10.1200/jco.2012.43.2229
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Procarbazine, Lomustine, and Vincristine Chemotherapy in Newly Diagnosed Anaplastic Oligodendroglioma: Long-Term Follow-Up of EORTC Brain Tumor Group Study 26951

Abstract: The addition of six cycles of PCV after 59.4 Gy of RT increases both OS and PFS in anaplastic oligodendroglial tumors. 1p/19q-codeleted tumors derive more benefit from adjuvant PCV compared with non-1p/19q-deleted tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
605
1
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,019 publications
(657 citation statements)
references
References 37 publications
17
605
1
17
Order By: Relevance
“…[4][5][6]  Anaplastic oligodendroglial tumors with 1p/19q co-deletions should no longer be treated with radiotherapy alone, but with alkylating agent chemotherapy, with or without radiotherapy. [4][5][6]  The introduction of molecular markers into the next WHO Classification of Tumors of the Nervous System is inevitable.…”
Section: Key Advancesmentioning
confidence: 99%
“…[4][5][6]  Anaplastic oligodendroglial tumors with 1p/19q co-deletions should no longer be treated with radiotherapy alone, but with alkylating agent chemotherapy, with or without radiotherapy. [4][5][6]  The introduction of molecular markers into the next WHO Classification of Tumors of the Nervous System is inevitable.…”
Section: Key Advancesmentioning
confidence: 99%
“…Chromosome 1p and 19q codeletion, the genetic hallmark of oligodendrogliomas associated with long survival and chemo-radio sensitivity, represents the prototype molecular marker with unequivocal diagnostic, prognostic, and therapeutic utilities in diffuse gliomas. [3][4][5][6][7] Isocitrate dehydrogenase (IDH) mutation is probably the most important molecular marker discovered in diffuse gliomas with breakthrough clinical values in the recent years. 8 Apart from its use in difficult diagnostic situations, [8][9][10] mutation of this enzyme also stratifies diffuse gliomas prognostically.…”
mentioning
confidence: 99%
“…Updated results of the primary analysis confirmed that disease control overall was mainly the same after RT or CT. 2 However, the secondary (and exploratory) analyses were perhaps the most intriguing and surprising. For example, despite the observation from other trials that (IDH mutation and) codeletion predicts the greatest chemosensitivity of anaplastic gliomas, 6,7 CT was, disappointingly to us, at best equi-efficacious as RT in the CIMP codel molecular subgroup of NOA-04. 2 An analogous observation was reported recently for (IDH mutant and) codeleted low-grade (WHO grade II) gliomas.…”
mentioning
confidence: 56%
“…In IDH mutant codeleted (ie, CIMP codel ) anaplastic gliomas, combined PCV and RT is clearly superior to RT alone 6,7 ; CT alone appears to be, at best, equi-efficacious with RT alone in both anaplastic 2 and low-grade gliomas. 8 Therefore, we agree with Wick et al, who are probably correct when they conclude by extrapolation that CT alone likely leads to shorter survival than combined CT and RT.…”
mentioning
confidence: 98%